Steering the Glycerol Electro‐Reforming Selectivity via Cation–Intermediate Interactions. (25th January 2022) - Wu, Jianxiang; Li, Jili; Li, Yefei; Ma, Xian‐Yin; Zhang, Wei‐Yi; Hao, Yaming; Cai, Wen‐Bin; Liu, Zhi‐Pan; Gong, Ming
Abstract: Electro‐reforming of renewable biomass resources is an alternative technology for sustainable pure H2 production. Herein, we discovered an unconventional cation effect on the concurrent formate and H2 production via glycerol electro‐reforming. In stark contrast to the cation effect via forming double layers in cathodic reactions, residual cations at the anode were discovered to interact with the glycerol oxidation intermediates to steer its product selectivity. Through a combination of product analysis, transient kinetics, crown ether trapping experiments, in situ IRRAS and DFT calculations, the aldehyde intermediates were discovered to be stabilized by the Li + cations to favor the non‐oxidative C−C cleavage for formate production. The maximal formate efficiency could reach 81.3 % under ≈60 mA cm −2 in LiOH. This work emphasizes the significance of engineering the microenvironment at the electrode–electrolyte interface for efficient electrolytic processes. Abstract : Glycerol oxidation selectivity can be efficiently steered via cation–intermediate interactions, resulting in highly selective glycerol electro‐reforming into hydrogen and formate. This work emphasizes the significance of engineering the microenvironment at the electrode–electrolyte interface for efficient electrochemical processes.